2014
DOI: 10.1088/0004-637x/782/1/33
|View full text |Cite
|
Sign up to set email alerts
|

THE PAN-STARRS1 MEDIUM-DEEP SURVEY: THE ROLE OF GALAXY GROUP ENVIRONMENT IN THE STAR FORMATION RATE VERSUS STELLAR MASS RELATION AND QUIESCENT FRACTION OUT TOz∼ 0.8

Abstract: Using a large optically-selected sample of field and group galaxies drawn from the Pan-STARRS1 Medium-Deep Survey (PS1/MDS), we present a detailed analysis of the specific star formation rate (SSFR) -stellar mass (M * ) relation, as well as the quiescent fraction versus M * relation in different environments. While both the SSFR and the quiescent fraction depend strongly on stellar mass, the environment also plays an important role. Using this large galaxy sample, we confirm that the fraction of quiescent gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
62
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 98 publications
12
62
1
2
Order By: Relevance
“…-mass relations found here is consistent with several observational studies and large-scale hydrodynamical simulations, showing that, on average, many properties of starforming galaxies that are related to star-formation activity (such as color, SFR, sSFR, and SFR-mass relation) are independent of their host environment, a result that appears to hold regardless of the redshift, the method used to define environment, and the star-formation activity indicator (Peng et al 2010;Muzzin et al 2012;Wijesinghe et al 2012;Koyama et al 2013Koyama et al , 2014Darvish et al 2014;Hayashi et al 2014;Lin et al 2014;Vogelsberger et al 2014;Cen 2014). Hence, it has been argued that the major role of environment is to control the fraction of quiescent and star-forming systems (Peng et al 2010;Sobral et al 2011;Muzzin et al 2012;Darvish et al 2014;Vogelsberger et al 2014), that is, it is more likely for galaxies to become quenched in denser environments.…”
Section: Line Ewsupporting
confidence: 90%
“…-mass relations found here is consistent with several observational studies and large-scale hydrodynamical simulations, showing that, on average, many properties of starforming galaxies that are related to star-formation activity (such as color, SFR, sSFR, and SFR-mass relation) are independent of their host environment, a result that appears to hold regardless of the redshift, the method used to define environment, and the star-formation activity indicator (Peng et al 2010;Muzzin et al 2012;Wijesinghe et al 2012;Koyama et al 2013Koyama et al , 2014Darvish et al 2014;Hayashi et al 2014;Lin et al 2014;Vogelsberger et al 2014;Cen 2014). Hence, it has been argued that the major role of environment is to control the fraction of quiescent and star-forming systems (Peng et al 2010;Sobral et al 2011;Muzzin et al 2012;Darvish et al 2014;Vogelsberger et al 2014), that is, it is more likely for galaxies to become quenched in denser environments.…”
Section: Line Ewsupporting
confidence: 90%
“…In our previous study, Lin et al (2014), we confirmed that the group environment strongly affects the fraction of quiescent galaxies at fixed stellar mass, but no environmental dependence was found for the star-forming sequence, in good agreement with previous works (Balogh et al 2004;Vulcani et al 2010;Koyama et al 2013). The result thus supports a fast environmentquenching scenario and favors galaxy mergers in groups as the primary quenching mechanism.…”
Section: Introductionsupporting
confidence: 92%
“…We hence extend our previous results to include the discussion of galaxy properties in terms of the projected group-centric radius r p and aim to understand at which radius the possible quenching mechanisms acting on galaxies effectively alter galaxy properties. This work is based on the same group catalog of two PS1 medium-deep fields, MD04 and MD07, produced by the probability friends-offriends (or PFOF) algorithm in Lin et al (2014). By taking advantage of the stacking technique plus background subtraction and removal of the field contamination, we obtain a finer correction for our stacked samples and thus more robust results than in our previous work.…”
Section: Introductionmentioning
confidence: 99%
“…From these same surveys it is possible to learn something about the evolving role of environment from measurements of local density or group catalogues (e.g. Giodini et al 2009;George et al 2011a;Knobel et al 2013;Lin et al 2014). In the context of the halo model (e.g.…”
mentioning
confidence: 99%